Preparation of EGCG decorated, injectable extracellular vesicles for cartilage repair in rat arthritis. Issue 6 (18th November 2021) - Song, Changwei; Xu, Shibo; Chang, Linna; Zhao, Xingjun; Mei, Xifan; Ren, Xiuli; Chen, Zhenhua
Abstract: Arthritis is a kind of chronic inflammatory autoimmune disease, which can destroy joint cartilage and bone, leading to joint pain, joint swelling, and limited mobility. Traditional therapies have many side effects or focus too much on anti-inflammation while neglecting joint repair. In this experiment, we combined Epigallocatechin gallate (EGCG) with extracellular vesicles derived from macrophages to treat rheumatoid arthritis. Sustained-release resulted in a significant decrease in chondrocyte expression of hypoxia-inducible factor 1-alpha, a decrease in apoptosis-related proteins Cytochrome C, Caspase-3, Caspase-9, and Bax. Molecular biological analysis showed that extracellular vesicles-encapsulated EGCG (EVs-EGCG) more significantly upregulated type II collagen expression by about 1.8-fold than EGCG alone, which was more beneficial for arthritis repair. Animal experiments revealed that these EGCG-coated extracellular vesicles significantly reduced swelling, decreased synovial hyperplasia, repaired cartilage, and attenuated arthritis-related pathology scores in arthritic rats. Measurement data showed that EVs-EGCG treatment reduced joint swelling by approximately 39.5% in rheumatoid rats. In vitro studies have shown that this EVs-EGCG can increase the expression of cartilage type II collagen and reduce apoptosis of chondrocytes. Moreover, it was demonstrated in vivo experiments to reduce cartilage destruction in rheumatoid arthritis rats, providing a solution for the treatment of rheumatoid arthritis.